A population-based, retrospective, cohort study of esophageal cancer missed at endoscopy - Chadwick, Georgina; Groene, Oliver; Hoare, Jonathan; Hardwick, Richard H.; Riley, Stuart; Crosby, Tom D.; Hanna, George B.; Cromwell, David A. (Endoscopy, 2014)
Background and study aims: Several studies have suggested that a significant minority of esophageal cancers are missed at endoscopy The aim of this study was to estimate the proportion of esophageal cancers missed at endoscopy on a national level, and to investigate the relationship between miss rates and patient and tumor characteristics.Patients and methods: This retrospective, population-based, cohort study identified patients diagnosed with esophageal cancer between April 2011 and March 2012 in England, using two linked databases (National Oesophago-Gastric Cancer Audit and Hospital Episode Statistics). The main outcome was the rate of previous endoscopy within 3 – 36 months of cancer diagnosis. This was calculated for the overall cohort and by patient characteristics, including tumor site and disease stage. Results: A total of 6943 new cases of esophageal cancer were identified, of which 7.8 % (95 % confidence interval 7.1 – 8.4) had undergone endoscopy in the 3 – 36 months preceding diagnosis. Of patients with stage 0/1 cancers, 34.0 % had undergone endoscopy in the 3 – 36 months before diagnosis compared with 10.0 % of stage 2 cancers and 4.5 % of stage 3/4 cancers. Of patients with stage 0/1 cancers, 22.1 % were diagnosed after ≥ 3 endoscopies in the previous 3 years. Patients diagnosed with an upper esophageal lesion were more likely to have had an endoscopy in the previous 3 – 12 months (P = 0.040). The most common diagnosis at previous endoscopy was an esophageal ulcer (48.2 % of investigations). Conclusion: Esophageal cancer may be missed at endoscopy in up to 7.8 % of patients who are subsequently diagnosed with cancer. Endoscopists should make a detailed examination of the whole esophageal mucosa to avoid missing subtle early cancers and lesions in the proximal esophagus. Patients with an esophageal cancer may be misdiagnosed as having a benign esophageal ulcer.